2008
DOI: 10.1186/1471-2458-8-331
|View full text |Cite
|
Sign up to set email alerts
|

Bed net ownership, use and perceptions among women seeking antenatal care in Kinshasa, Democratic Republic of the Congo (DRC): Opportunities for improved maternal and child health

Abstract: Background: To describe malaria knowledge, attitudes toward malaria and bed net use, levels of ownership and use of bed nets, and factors associated with ownership and use among pregnant women attending their first antenatal care (ANC) visit in Kinshasa, DRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 27 publications
4
39
2
Order By: Relevance
“…The mother/guardian's educational level and knowledge were found to be associated with a net being used, as in other studies [1,10,16-18]. This analysis found that the odds of a net being used in a household where the mother/guardian had at least 10 years of education were 2.32 compared to a net owned by a respondent with no education.…”
Section: Discussionsupporting
confidence: 74%
“…The mother/guardian's educational level and knowledge were found to be associated with a net being used, as in other studies [1,10,16-18]. This analysis found that the odds of a net being used in a household where the mother/guardian had at least 10 years of education were 2.32 compared to a net owned by a respondent with no education.…”
Section: Discussionsupporting
confidence: 74%
“…Perceived utilization of LLITN is higher in the present study as compared to the findings of other literatures[20-22]. The control villages were better in the perceived utilization of LLITN than the intervention Gots .…”
Section: Discussioncontrasting
confidence: 66%
“…This fi nding is similar to that of Adonga (2005) in Ghana where poor knowledge of malaria was associated with non utilization of ITNs. It is also similar to fi ndings of Pettifor (2008) in Kinshasha, Democratic Republic of Congo, where women with secondary or higher education were 2.8 times more likely to use an ITN compared to women with less education . However, it is contrary to fi ndings by Natalie et al (2006) in Ghana where greater knowledge of malaria was not associated with improved ITN use.…”
Section: Discussionsupporting
confidence: 71%
“…One possible explanation for this fi nding is that formal education enables individuals to better understand a disease, its dangers, susceptibility to it and to take necessary preventive action against the disease. However, on a contrary note, the fi ndings of Pettifor (2008) in Democratic Republic of Congo revealed that education was not associated with ITN use.…”
Section: Discussionmentioning
confidence: 72%